Theoretical And Practical Aspects of Crime Prevention in the Field of Personal Data - Choriev Anvar Kuzievich (Scientific Trends, 2026)
The article examines the theoretical and methodological foundations of crime prevention and reveals its significance in the life of society. The role of studies on the causes of crime, conditions facilitating its commission, the mechanism of individual criminal behavior, and criminological forecasting within the system of crime prevention is analyzed. The author refers to the scientific and philosophical origins of the idea of crime prevention, highlighting the views of foreign thinkers who assigned priority importance to preventive activities. Furthermore, the article clarifies the correlation and distinction between the concept of crime prevention and general and special prevention, and characterizes social, criminological, and individual types of preventive measures. Particular attention is paid to substantiating that an increase in the level of legal awareness and legal culture constitutes a key factor in preventing crimes related to violations of personal data legislation. It is emphasized that the level of crime is directly dependent on the state of legal culture in society. Based on an analysis of the content of the Decree of the President of the Republic of Uzbekistan aimed at enhancing legal awareness and legal culture, the article substantiates the necessity of ensuring systemic consistency and continuity in the education system, as well as forming legal immunity among young people.
Keywords: Crime, crime prevention, prevention, individual prevention, legal awareness, legal culture, personal data, rule of law, legal education of youth.